The potential for insect pollinators to alleviate global pollination deficits and enhance yield of fruit and seed crops - Garibaldi, Lucas Alejandro (2018)
Humanity faces amajor challenge as agricultural intensification and growth ofcultivated areas increase to satisfy greater demands from a humanpopulation of growing size and affluence. However, with long-term,sustainable agricultural practices, higher agricultural productiondoes not necessarily require further loss of biodiversity or majorenvironmental degradation. Crop yield (tonnes ha -1 ) is a key driverof farm profits, livelihoods and agricultural decisions, whichinfluence land use at both local and global scales. This chapterdiscussed how yield could be limited by pollen quantity and quality.Pollination deficit is the difference between realized yield andpotential achievedunder optimal pollen quantity and quality conditions. Pollinationdeficits can arise for crops because, unlike other limits, such asnutrients and pests, pollen delivery is not managed directly in mostagricultural systems. Consistent with these observations, globalpatterns of yield reveal that pollination deficits are common forcrops dependent on animal pollination.Pollination deficitsreduce the yield growth of pollinator-dependent crops and alsopromote thecultivation of alarger area to satisfy production demands. Indeed, planting ofpollinator-dependentcrops is expandingthree times faster than the managed honey bee population, potentiallyexacerbating chronic pollination deficits exhibited by many crops. Asa consequence, crop yield increasingly depends on pollinationservices provided by wild insects, which contribute significantly tofruit or seed set, regardless of crop origin (exotic or native) andlife history traits (herbaceous or woody, etc.). Honey beessupplement the role of wild insects but cannot replace them, so thatefforts to maximize pollination require the conservation orenhancement of all available pollinators. However, managed and wildpopulations of pollinators are declining in many agriculturallandscapes, and further introductions of alien species should bediscouraged because of their manifold environmental impacts. Thissituation strongly motivates conservation or restoration of naturaland semi-natural areas within agricultural landscapes.p { margin-bottom: 0.25cm; line-height: 120%; }